Investigating the Effects of Reconstruction Conditions on Image Quality and Radiomic Analysis in Photon-counting Computed Tomography - Miyu Ohata; Ryohei Fukui; Yusuke Morimitsu; Daichi Kobayashi; Takatsugu Yamauchi; Noriaki Akagi; Mitsugi Honda; Aiko Hayashi; Koshi Hasegawa; Katsuhiro Kida; Sachiko Goto; Takao Hiraki (Journal of Medical Physics)
Introduction: Photon-counting computed tomography (CT) is equipped with an adaptive iterative reconstruction method called quantum iterative reconstruction (QIR), which allows the intensity to be changed during image reconstruction. It is known that the reconstruction conditions of CT images affect the analysis results when performing radiomic analysis. The aim of this study is to investigate the effect of QIR intensity on image quality and radiomic analysis of renal cell carcinoma (RCC). Materials and Methods: The QIR intensities were selected as off, 2 and 4. The image quality evaluation items considered were task-based transfer function (TTF), noise power spectrum (NPS), and low-contrast object specific contrast-to-noise ratio (CNRLO). The influence on radiomic analysis was assessed using the discrimination accuracy of clear cell RCC. Results: For image quality evaluation, TTF and NPS values were lower and CNRLO values were higher with increasing QIR intensity; for radiomic analysis, sensitivity, specificity, and accuracy were higher with increasing QIR intensity. Principal component analysis and receiver operating characteristics analysis also showed higher values with increasing QIR intensity. Conclusion: It was confirmed that the intensity of the QIR intensity affects both the image quality and the radiomic analysis.